Metode Compic untuk Meningkatkan Bahasa Resptif pada Anak Autis - Lisfarika Napitupulu; MG. Adiyanti (JIP (Jurnal Intervensi Psikologi), 2010)
Low communication skills in children with autism are caused by obstruction of their receptive language skills. To Increase receptive language skill, can be done by the compic method. The goal of this research is to demonstrate the effectiveness of compic method in increasing receptive language skills in autistic child. This research used single case study with one subject, where the A-B-A model research design applied. Participants in this research is a boy aged 7 years and 5 months and diagnosed with autism. This research shows that the compic method could increase reseptive language in identifying nouns and objects. Factors that support the effectiveness of the intervention are subjects that is relatively still young, support form the teacher who understand the children's condition and needs, the school's system that facilitate the development of of the subjects ability, and the intensity of the intervention.Â Keywords: autis, receptive language, compic